Activity of 2,4-Diaminoquinazoline Compounds against Candida species - Castaldo, Robert A. (1979)
Forty recent clinical isolates of three different Candida sp. were tested in the microtiter system for susceptibility to two new 2,4-diaminoquinazoline (DAQ) compounds, amphotericin B and flucytosine. The two DAQ preparations showed activity similar to amphotericin B and flucytosine. The geometric mean minimal inhibitory concentrations for these four drugs were as follows: DAQ 1A, 0.64 μg/ml; DAQ 2A, 1.39 μg/ml; amphotericin B, 1.03 μg/ml; and flucytosine, 0.72 μg/ml. An additional seven DAQ compounds were tested but showed less or no activity against 17 Candida isolates. Forty-eight-hour viability studies with DAQ 2A alone or in combination with amphotericin B, flucytosine, or sulfamethoxazole were carried out with one isolate of intermediate susceptibility to each of these agents except sulfamethoxazole. For this isolate the combination of DAQ 2A and sulfamethoxazole was synergistic, and the combination of DAQ 2A and AMB was either synergistic or additive, whereas the combination of DAQ 2A and flucytosine was antagonistic. Although regrowth of cultures exposed to DAQ 2A was noted over a 48-h period, neither degradation of the drug nor development of resistance to the drug could be detected. Swiss white mice receiving DAQ 1A at a dose of 6 mg/kg for 5 days showed no obvious signs of toxicity, including weight loss.